KEGAGALAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI WILAYAH PUSKESMAS MANGGIS I KARANGASEM - Arya Mahendra Yogantara (Intisari Sains Medis, 2015)
One of many efforts to improve nutrition status of baby is by giving milk the mother (breastfeeding).Breastfeeding containing antibodies from the mother who helped fight against disease, for that provision of breastfeeding in infants should be done early and given exclusively.The department of health through a decree of the minister of health no: 450 / menkes / sk / iv / 2004 determined that all health workers to inform all the mothers that just given birth to give breast-fed exclusively.The aim of this research is to find a failure and the knowledge about granting exclusive breast-fed in the work area of Manggis IKarangasem primary health care.The total sample used as much as 50 people with the criteria for all the mothers that having a baby was 0-6 months fail to provide exclusive breastfeeding in the work area of Manggis I primary health care.Cross sectional design is used in descriptive observational research. This research take place from september until october 2013. The result was obtained the decision makers when mom give supplementary food breastfeeding who mentors be the cause of failure is own health officers as many as 56 % and the second was the decision of the mother own about 54 %.The mother’s knowledge regarding breastfeeding exclusive been gained knowledge less ( 46 % ) knowledge enough ( 28 % ) and knowledge of good ( 26 % ).